2016
DOI: 10.1007/s12011-016-0795-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment the Exposure Level of Rare Earth Elements in Workers Producing Cerium, Lanthanum Oxide Ultrafine and Nanoparticles

Abstract: In order to assess occupational exposure level of 15 rare earth elements (REEs) and identify the associated influence, we used inductively coupled plasma mass spectrometry (ICP-MS) based on closed-vessel microwave-assisted wet digestion procedure to determinate the concentration of Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu in urinary samples obtained from workers producing ultrafine and nanoparticles containing cerium and lanthanum oxide. The results suggest that La and Ce were the primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Rare-earth elements (REE) mining and processing can be mentioned in this respect, although the reports on the occupational exposure associated with negative health outcomes other than pneumoconiosis are sporadic. Li et al found higher urinary levels of La, Nd, Ce and Gd in exposed workers dealing with Ce and La oxides ultrafine particles and nanoparticles compared to non-exposed 31 , however the next paper from the group (presumably on the same subjects), on creatinine adjusted urinary levels of REEs, did not show significant difference in gadolinium levels 32 . We were unable to find reports on deposition of gadolinium in occupationally exposed subjects.…”
Section: Discussionmentioning
confidence: 88%
“…Rare-earth elements (REE) mining and processing can be mentioned in this respect, although the reports on the occupational exposure associated with negative health outcomes other than pneumoconiosis are sporadic. Li et al found higher urinary levels of La, Nd, Ce and Gd in exposed workers dealing with Ce and La oxides ultrafine particles and nanoparticles compared to non-exposed 31 , however the next paper from the group (presumably on the same subjects), on creatinine adjusted urinary levels of REEs, did not show significant difference in gadolinium levels 32 . We were unable to find reports on deposition of gadolinium in occupationally exposed subjects.…”
Section: Discussionmentioning
confidence: 88%
“…To date, very few measurements of the trace elemental composition of indoor and outdoor PM 2.5 have been performed for United States’ schools, although more data are available for homes and residential buildings. These studies have largely focused on representative and transition elements, with one study showing the indoor enrichment of several elements including hazardous air pollutants such as Sb and Pb . In contrast, a unique aspect of Houston area aerosols is their lanthanoid (i.e., rare earths) enrichment emanating from fluid catalytic cracking (FCC) units. ,,, Airborne rare earth elements are readily absorbed by humans , leading to a variety of toxicological symptoms . Additionally, children exposed to refinery emissions exhibit increased wheezing, bronchial inflammation, reduced lung function and other symptoms , necessitating this research.…”
Section: Introductionmentioning
confidence: 99%
“…25 In contrast, a unique aspect of Houston area aerosols is their lanthanoid (i.e., rare earths) enrichment emanating from fluid catalytic cracking (FCC) units. 13,14,18,20 Airborne rare earth elements are readily absorbed by humans 30,31 leading to a variety of toxicological symptoms. 32 Additionally, children exposed to refinery emissions exhibit increased wheezing, bronchial inflammation, reduced lung function and other symptoms 33,34 necessitating this research.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Li et al (2016) found higher levels of La, Ce, Nd, and Gd in the urine of workers manufacturing cerium and lanthanum oxide ultrafine and nano-sized particles. Li et al (2017) found higher levels of La and Ce in the urine of the same kind of workers. The levels of Y, La, Ce, Pr, Nd, and Sm were higher in the urine of children living near the Bayan Obo mining area (Liang et al, 2018).…”
Section: Introductionmentioning
confidence: 70%
“…Li et al (2016) explored a sensitive and reliable indicator of the exposure level to REEs in urines. Li et al (2017) identified the occupational exposure to REEs by analyzing urines using ICP-MS based on closed-vessel, microwave-assisted wet digestion. Bettinelli et al (2002) developed a method with electrothermal vaporization ICP-MS (ETV-ICPMS) for determining REEs in urine, in which the sample was injected into the graphite tube and trifluoromethane (Freon-23) and was used as a chemical modifier to reduce vaporization temperature and the memory effect of most of the lanthanides.…”
Section: Introductionmentioning
confidence: 99%